Learning Video Applications on Global Warming Materials: Analysis of Differences on Students’ Cognitive Learning Outcomes - Hayati, Nur; Fitriyah, Lina Arifah (Jurnal Pendidikan MIPA, 2022)
videos make science concepts more concrete so that the students understand the material more easily. This study aimed to explain the differences in students’ cognitive learning outcomes through the application of learning videos on Global Warming material. This research was a quantitative research with a quasi-experimental method. The research design was a posttest only control design. The samples of this research were students of class VII-B SMP A. Wahid Hasyim Jombang as the control class and class VII-C as the experimental class. The research instrument was a test for cognitive learning outcomes. The data were analyzed by prerequisite test, then, followed by hypothesis testing using Independent Samples Test. The analysis results showed that the score of sig. (2-tailed) 0.000 < 0.05, so that there was a significant difference between the cognitive learning outcomes of the experimental class and the control class. It was concluded that there were differences between students’ cognitive learning outcomes taught using videos and Power Point media.Keywords: learning media of video, global warming, cognitive learning outcomesDOI: http://dx.doi.org/10.23960/jpmipa/v23i1.pp222-233